2017
DOI: 10.1108/jea-06-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and accountability in schools serving disadvantaged communities

Abstract: Purpose Increased school autonomy and accountability have been a common denominator of national reforms in otherwise heterogeneous governance systems in Europe and the USA. The paper argues that because schools serving disadvantaged communities (SSDCs) often have lower average performance, they are more often sanctioned or under closer scrutiny, but might also receive more additional resources. The purpose of this paper is to therefore analyze whether SSDCs have more or less autonomy than schools with a more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
15
1
1
Order By: Relevance
“…For example, Møller and Schratz (2008) showed that Scandinavian countries have a strong tradition of viewing schooling through a lens of democratic ideal. Klein (2017) noted that Finland has a decentralized governance system where municipalities have the most responsibility in schooling decisions. Finnish teachers have high levels of autonomy in developing the curriculum at the local level within the criteria of the national curricula, and the final exit exam in upper secondary level is the only standardized assessment that all students take (Hendrickson, 2015;Sahlberg, 2010).…”
Section: Logics Of Accountability In Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Møller and Schratz (2008) showed that Scandinavian countries have a strong tradition of viewing schooling through a lens of democratic ideal. Klein (2017) noted that Finland has a decentralized governance system where municipalities have the most responsibility in schooling decisions. Finnish teachers have high levels of autonomy in developing the curriculum at the local level within the criteria of the national curricula, and the final exit exam in upper secondary level is the only standardized assessment that all students take (Hendrickson, 2015;Sahlberg, 2010).…”
Section: Logics Of Accountability In Educationmentioning
confidence: 99%
“…Test-based logic can be supported by market principles, which prioritize competition, choice, and efficiency (McDermott, 2011). Under market principals, schools have extensive autonomy in multiple areas so that schools compete for students and resources (Klein, 2017). For example, in the US, test-driven external accountability policies were adopted across states under the NCLB Act and the federal Race to the Top (RTTT) program.…”
Section: Logics Of Accountability In Educationmentioning
confidence: 99%
See 3 more Smart Citations